2020
DOI: 10.33225/pec/20.78.884
|View full text |Cite
|
Sign up to set email alerts
|

Distance Education During Covid-19: The Perspective of Slovak Teachers

Abstract: As the new coronavirus SARS-CoV-2 (causing COVID-19) has begun to spread around the world, education has taken the form of distance education from one day to the next. To this day, little is known about distance education during the pandemic period from teachers’ point of view, so the study focused on perception and management of distance education in primary school (primary and lower secondary education) and upper-secondary school (upper secondary education) teachers; and the main aim was to explore the conne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Some of them were forced to, over a very short period of time, learn how to use the most modern educational technology for distance education, to use tools to design educational material (Word, Excel, PowerPoint), and to under inadequate circumstances (problems regarding the availability of technology) prepare educational material which was electronically sent to their students. In addition, in some cases there was a lack of support from the educational environment, and the teachers were often, due to an increased workload and problems pertaining to the preparation of educational material, exposed to stress (Ballova Mikuškova & Verešova, 2020;Lautenbach & Randell, 2020;Wilson & Christopher, 2008). This was also confirmed by the research results of the Institute for the Improvement of Education of the Republic of Serbia.…”
Section: Discussionmentioning
confidence: 99%
“…Some of them were forced to, over a very short period of time, learn how to use the most modern educational technology for distance education, to use tools to design educational material (Word, Excel, PowerPoint), and to under inadequate circumstances (problems regarding the availability of technology) prepare educational material which was electronically sent to their students. In addition, in some cases there was a lack of support from the educational environment, and the teachers were often, due to an increased workload and problems pertaining to the preparation of educational material, exposed to stress (Ballova Mikuškova & Verešova, 2020;Lautenbach & Randell, 2020;Wilson & Christopher, 2008). This was also confirmed by the research results of the Institute for the Improvement of Education of the Republic of Serbia.…”
Section: Discussionmentioning
confidence: 99%
“…In Slovakia, where the present study was conducted, almost 40% of a representative sample reported feeling very threatened by the COVID-19, with higher levels of perceived threat reported especially by women and older people (MNFORCE et al, 2020). A survey with Slovak teachers reported an overall increase in negative feelings (e.g., feeling upset, scared, afraid) during the COVID-19 pandemic period (Ballová Mikušková & Verešová, 2020). A recent meta-analysis shows the prevalence of anxiety during the COVID-19 pandemic to be almost 32% (Salari et al, 2020) based on samples from all over the world.…”
Section: Introductionmentioning
confidence: 99%
“…Explicit danger such COVID-19 paired with uncertainty is known to be associated with increased negative emotions and anxiety [ 31 , 32 ]. A survey of Slovak teachers reported an overall increase in negative feelings (e.g., feeling upset, scared, afraid) during the COVID-19 pandemic period [ 33 ]. Symptoms such as anxiety, depression, fear, stress, and sleep problems were also seen more frequently during the COVID-19 pandemic [ 34 ], and a recent meta-analysis showed the prevalence of anxiety during the COVID-19 pandemic to be almost 32% [ 2 ] based on samples from all over the world.…”
Section: Discussionmentioning
confidence: 99%